2012
DOI: 10.2217/pgs.12.152
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of Opioids and Perioperative Pain Management

Abstract: Inadequate pain relief and adverse effects from analgesics remain common in children and adults during the perioperative period. Opioids are the most commonly used analgesics in children and adults to treat perioperative pain. Narrow therapeutic index and a large interpatient variability in response to opioids are clinically significant, with inadequate pain relief at one end of the spectrum and serious side effects, such as respiratory depression and excessive sedation due to relative overdosing, at the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 179 publications
1
50
0
1
Order By: Relevance
“…The relation between the analyzed SNPs in OPRM1 and COMT on morphine requirement has also been illustrated in different adult studies with postoperative [19,[21][22][23][24][25]37] and cancer related pain [38][39][40], although others failed in finding these associations [41][42][43]. This failure is most likely caused by the polygenic aspect in pain [10], as discussed in the introduction. Our results on the combined genotypic effect are in line with two previously performed studies, in which is concluded that OPRM1 118AA in combination with COMT 158 met have the lowest requirement whereas vice versa (118G and COMT 158 val) have a higher risk for more pain and thus more opioid consumption [20,30].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The relation between the analyzed SNPs in OPRM1 and COMT on morphine requirement has also been illustrated in different adult studies with postoperative [19,[21][22][23][24][25]37] and cancer related pain [38][39][40], although others failed in finding these associations [41][42][43]. This failure is most likely caused by the polygenic aspect in pain [10], as discussed in the introduction. Our results on the combined genotypic effect are in line with two previously performed studies, in which is concluded that OPRM1 118AA in combination with COMT 158 met have the lowest requirement whereas vice versa (118G and COMT 158 val) have a higher risk for more pain and thus more opioid consumption [20,30].…”
Section: Discussionmentioning
confidence: 95%
“…The field of pharmacogenetics predicts individual dosing of drugs based on genetic differences affecting disposition and effect. Genetic polymorphisms in several genes have been associated with pain sensitivity and opioid response in both adults [10,11] and children [12]. More recently, genetic variation in newborns with the neonatal abstinence syndrome (NAS) caused by in utero opioid exposure has been related to treatment requirement and length of hospitalization [13].…”
mentioning
confidence: 99%
“…The role of pharmacogenomics continues to be investigated and a number of excellent reviews are available [75][76][77][78][79]. While each isolated pharmacogenomics influence may be discerned, the complex interplay of all these influences in any one individual makes clinical interpretation difficult.…”
Section: Pharmacogenomicsmentioning
confidence: 99%
“…Polymorphisms in ABCB1, the gene that codes for the effl ux transporter P-glycoprotein, have been shown to have a signifi cant eff ect on the pharmacokinetics of opioids by restricting uptake or enhancing clearance ( 34 ). Variability in ABCB1 has been found to infl uence daily methadone dosage, providing further support for its role in opioid drug transport ( 35 ).…”
Section: Molecular and Genetic Factors Infl Uencing Opioid Activitymentioning
confidence: 99%
“…Polymorphisms in metabolic enzymes, including UDP-glucuronosyl transferase and cytochrome P450 (CYP) 2D6 and CYP3A4, also appear to infl uence the pharmacokinetics of opioids in humans ( 34 ). Specifi cally, UDP-glucuronosyl transferase is involved in metabolizing morphine to the active metabolites morphine-6-glucuronide and morphine-3-glucuronide; variations in the gene coding for this enzyme have been found to correlate with morphine and morphine metabolite concentrations in the serum ( 35 ).…”
Section: Molecular and Genetic Factors Infl Uencing Opioid Activitymentioning
confidence: 99%